One Visit Relining Procedure in Patient with Loss of Vertical Dimension - Niko Falatehan; Rebecca Gandhanya (Scientific Dental Journal, 2018)
Background: Dentists often encounter patients with worn dentures that still feel comfortable even though the patients have lost the supporting tissue heights due to physiological and pathological resorption. Loss of denture retention, stability, and occlusal vertical dimension are most often caused by alveolar bone resorption. Dentures that are loose because of poor adaption to the supporting tissues should be relined. Chair-side procedures provide immediate resolution, avoiding the edentulous period of time accompanying laboratory relines. Case Report: A 70-year-old male edentulous patient came to the Prosthodontic Clinic, Faculty of Dentistry, Trisakti University, Jakarta, Indonesia. The patient had been wearing the upper and lower dentures for approximately eight years. The patient had alveolar ridge resorption, which causes loss of retention, stability and vertical dimension. After the problems were thoroughly diagnosed and corrected, a chair-side denture relining with an open-mouth technique was used. Conclusion: Direct relining in a single visit helped the complete denture to regain its retentiveness, allowing for prolonged the use of the worn denture. It also adjusted occlusal vertical dimension to improve the occlusal support and esthetics.